Women artisanal miners in the Gold Mining industry of Bondo Sub-County, Western Kenya and their navigation of their productive and reproductive labour during the COVID-19 pandemic during 2020 - Yieke, Tess (Department of Sociology, 2025)
The COVID-19 pandemic and related restrictions profoundly impacted Africa's artisanal mining sector, leading to operational disruptions, market closures, health issues, security concerns, and increased economic vulnerabilities. Plummeting mineral prices exacerbated challenges, deepening poverty among artisanal miners. The pandemic heightened their precarious conditions, leaving them more vulnerable to economic shocks with limited access to resources and stability. Despite extensive research on the pandemic's impact on artisanal miners, few studies examine it through a gendered lens. Gender inequalities in mineral-rich developing nations intensified during the pandemic, disproportionately affecting women. The limited literature on the subject indicates reduced working hours and income, restricted access to essential resources, heightened gender- based violence, and an increased burden of unpaid reproductive labour for women due to COVID-19 related measures. This study explored the challenges faced by women artisanal miners during the pandemic and their coping mechanisms. Ten women from Ndira Market and Ka-June mines in Bondo Sub-County, Western Kenya, were interviewed. Using the feminist economic conceptual framework, the analysis revealed productive labour challenges, such as reduced working hours and declining gold prices, and unpaid reproductive labour challenges, including increased living costs and inadequate support. Coping mechanisms involved bribery, alternative employment, seeking informal loans, prioritizing essential items, bringing children to the mines, and receiving childcare assistance from family and community members. These findings underscore a central argument within this thesis: women artisanal miners play an indispensable role in artisanal mining communities. The socio-economic crisis triggered by the COVID-19 pandemic underscores their significance, highlighting their crucial contributions to sustaining the local artisanal mining industry through their mining activities, and supporting the broader artisanal mining community through their unpaid social reproductive labour within their households. Consequently, supporting and uplifting women artisanal miners can catalyse overall improvements in the industry and enhance the community's well-being.